How language evolved from manual gestures. - Corballis, Michael C. (Gesture, 2012)
Several lines of evidence suggest that human language originated in manual gestures, not vocal calls. These are the ability of nonhuman primates to use manual action flexibly and intentionally, the nature of the primate mirror system and its homology with the language circuits in the human brain, the relative success in teaching apes to communicate manually rather than vocally, the ready invention of sophisticated signed languages by the deaf, the critical role of pointing in the way young children learn language, and the correlation between handedness and cerebral asymmetry for language. A gradual switch from manual to facial and vocal expression may have occurred late in hominin evolution, with speech reaching its present level of autonomy only in our own species, Homo sapiens.